2006
DOI: 10.1111/j.1474-919x.2006.00550.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of migration strategy and food availability on White StorkCiconia ciconiabreeding success

Abstract: In the mid 1970s, the breeding populations of the migrant White Stork Ciconia ciconia were close to extinction in the northeastern region of France (Alsace). A re‐introduction project was implemented, resulting in the year‐round settlement of some individuals in the region, which rely on additional food supplied by humans during the winter. Today, both resident and migrant birds breed in the same areas and take food from rubbish dumps and humans (farmers). The effects of these anthropogenic influences, alterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 24 publications
1
69
2
Order By: Relevance
“…This hypothesis was also supported by food supplementation experiments which demonstrated that, at least in some populations, reproductive success of white storks is limited by the food availability during the breeding season (Djerdali et al 2008). Similarly, it was found that stork pairs occupying territories with unlimited anthropogenic food supplies and negligible intra-specific competition (e.g., near rubbish dumps) had higher reproductive success in comparison to pairs that exploited natural food resources, even if their territories were of good quality (Tortosa et al 2002;Massemin-Challet et al 2006). We also found a tendency for the negative density-dependent effects to occur during the years of delayed population arrival at breeding grounds, which further supports the link between the phenology of spring migration and spatial patterns of productivity within the populations of white stork.…”
Section: Discussionmentioning
confidence: 78%
“…This hypothesis was also supported by food supplementation experiments which demonstrated that, at least in some populations, reproductive success of white storks is limited by the food availability during the breeding season (Djerdali et al 2008). Similarly, it was found that stork pairs occupying territories with unlimited anthropogenic food supplies and negligible intra-specific competition (e.g., near rubbish dumps) had higher reproductive success in comparison to pairs that exploited natural food resources, even if their territories were of good quality (Tortosa et al 2002;Massemin-Challet et al 2006). We also found a tendency for the negative density-dependent effects to occur during the years of delayed population arrival at breeding grounds, which further supports the link between the phenology of spring migration and spatial patterns of productivity within the populations of white stork.…”
Section: Discussionmentioning
confidence: 78%
“…However, even among the well-studied examples such as Eurasian blackcaps Sylvia atricapilla (Plummer et al, 2015) and white storks Ciconia ciconia (Massemin-Challet et al, 2006), it is difficult to disentangle various other potential influences such as the effects of climate change.…”
Section: Feeding and Dependencymentioning
confidence: 99%
“…Schulz 1998;Massemin-Challet et al 2006;Djerdali et al 2008;Kosicki 2010;Vergara et al 2010). We found that the number of eggs was best explained by the arrival date of the second stork at the nest, rather than by local weather or land cover.…”
Section: Discussionmentioning
confidence: 87%
“…Due to their low thermoregulation abilities during the first 3 weeks after hatching, the semi-altricial White Stork nestlings are particularly sensitive towards cold and wet weather conditions, which can lead to hypothermia (Tortosa and Castro 2003;Jovani and Tella 2004;Kosicki 2012;Gordo et al 2013), and make them more susceptile to diseases (Olias et al 2010). Favourable feeding conditions, on the other hand, promote White Stork reproductive outcome (Tortosa et al 2002;Massemin-Challet et al 2006;Hušek et al 2013) by stimulating both the number of eggs laid (Sasvári and Hegyi 2001;Djerdali et al 2008) as well as nestling development (Kosicki and Indykiewicz 2011). White Storks forage preferentially in wet open landscapes with short vegetation (Alonso et al 1991;Dziewiaty 2005), where their principal food consists of insects, earthworms, amphibians and voles (Antczak et al 2002).…”
Section: Introductionmentioning
confidence: 99%